Using a Proportional Approach to Taxation in Ukraine: Problems and Possible Ways of their Solution (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article analyzes the proportional (linear) approach to reforming the tax system of Ukraine in modern conditions, specified its shortcomings and suggested ways of introducing progressivity of the tax system in Ukraine based on the experience of foreign countries. This will ensure that the principle of justice, which so far does not adhere to the authorities.
Keywords: proportional taxes, equity in taxation, progressive taxes, tax reform, tax system of Ukraine, the Tax Code of Ukraine, the European Union, Slovakia